Respon Pertumbuhan Beberapa Varietas Bibit Kelapa Sawit di Pre-Nursery pada Kondisi Cekaman Kekeringan - Irawan, Hendra; Setyorini, Titin; Suryanti, Sri (AGROISTA : Jurnal Agroteknologi, 2025)
The objective of the study was to identify the responses of oil palm seedlings to drought stress conditions during pre-nursery cultivation. The research was conducted at two locations: the Maguwoharjo Educational and Research Field (Kebun Pendidikan dan Penelitian/KP2) and the Central Laboratory of the STIPER Yogyakarta Institute of Agriculture. The research was carried out from April to July 2021. A factorial experimental design with two factors arranged in a completely randomized design (CRD) was used in this study. The first factor consisted of three hybrid oil palm varieties: D×P SAIN-2 (V1), D×P SAIN-3 (V2), D×P SAIN-4 (V3). The second factor was the irrigation frequency or drought stress level, with three levels: watering once a day (F1), watering every 2 days (F2), and watering every 3 days (F3). The research data were analyzed using analysis of variance (ANOVA) at significant level of 5%. In the event of significant differences being identified among the treatments, further testing was conducted using Duncan's Multiple Range Test (DMRT) at a 5% significance level. The result showed that there was no significant interaction between different varieties and irrigation frequencies on oil palm seedling growth in the pre-nursery stage. However, the variety D×P SAIN-4 exhibited significant effect on stem diameter, leaf number, leaf area, and fresh stem weight. Under drought stress conditions, the best growth performance was observed in oil palm seedlings of the D×P SAIN-4, followed by the D×P SAIN-2. Additionally, irrigation frequency influenced stem diameter and leaf number. Overall, oil palm seedlings in the pre-nursery stage showed the best growth when watered once a day. In the pre-nursery cultivation stage, all oil palm seed varieties can tolerate watering every 2 (two) days